Methodological instructions for the implementation of the calculation and graphic task “Technical and economic efficiency of measures aimed at improving occupational safety in production” - Yevtushenko, Nataliіa Serhiivna; Tverdokhliebova, Natalia Yevheniivna (Національний технічний університет "Харківський політехнічний інститут", 2024)
Occupational safety audit is an independent objective assessment of the state of the enterprise’s labor protection system to determine the current level of safety at the enterprise, the main tasks of which are: identifying shortcomings in the enterprise’s labor protection system, labor assessment, analysis of compliance with the harmonization of labor protection documentation with the legislation of Ukraine, assessment of system effectiveness, detection of violations in the labor protection system, development of recommendations for the elimination of these violations.
Keywords: calculation and graphic task; methodological instructions; technical and economic efficiency; occupational safety in production; organizational and technical ensuring; professional safety of workplaces; labor protection; civil security"; охорона праці; аудит охорони праці; умови праці; безпека праці